Genetic variants, pathophysiological pathways, and oral anticoagulation in patients with hypertrophic cardiomyopathy and atrial fibrillation - Wang, Shengnan; Chen, He; Liu, Chunju; Wu, Mengxian; Sun, Wanlei; Liu, Shenjian; Zheng, Yan; He, Wenfeng (Frontiers in Cardiovascular Medicine, 2023)
Atrial fibrillation (AF) is commonly prevalent in patients with hypertrophic cardiomyopathy (HCM). However, whether the prevalence and incidence of AF are different between genotype-positive vs. genotype-negative patients with HCM remains controversial. Recent evidence has indicated that AF is often the first presentation of genetic HCM patients in the absence of a cardiomyopathy phenotype, implying the importance of genetic testing in this population with early-onset AF. However, the association of the identified sarcomere gene variants with HCM occurrence in the future remains unclear. How the identification of these cardiomyopathy gene variants should influence the use of anticoagulation therapy for a patient with early-onset AF is still undefined. In this review, we sought to assess the genetic variants, pathophysiological pathways, and oral anticoagulation in patients with HCM and AF.